Płyty Kratowe z Elementów Powtarzalnych - Gutkowski, W. (Engineering Transactions, 1965)
The displacement equation (3.6) is given for a regular three-dimensional bar system known under the name of unitstrut system. The problem is given a uniform treatment by means of the difference calculus, the segmental character of the system being preserved throughout the entire argument. In conclusion an example is given of a square plate loaded in a continuous manner and supported at four-points. The results are confronted with those of the experiments described in [4].